Soleus adaptation to combined exercise and heat acclimation: Physiogenomic aspects - Kodesh, E.; Horowitz, M. (Medicine & Science in Sports & Exercise, 2010)
Introduction: Adaptation to heat (acclimation [ACC]) and exercise training (EX) require global changes at all levels of body organization to enhance muscle performance. In this investigation, we combined these stressors and examined physiological and genomic aspects of adaptation in skeletal muscle (soleus).